2012
DOI: 10.1371/journal.pone.0038158
|View full text |Cite
|
Sign up to set email alerts
|

New Mutations in Chronic Lymphocytic Leukemia Identified by Target Enrichment and Deep Sequencing

Abstract: Chronic lymphocytic leukemia (CLL) is a heterogeneous disease without a well-defined genetic alteration responsible for the onset of the disease. Several lines of evidence coincide in identifying stimulatory and growth signals delivered by B-cell receptor (BCR), and co-receptors together with NFkB pathway, as being the driving force in B-cell survival in CLL. However, the molecular mechanism responsible for this activation has not been identified. Based on the hypothesis that BCR activation may depend on somat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…Genes such as BRAF and MLL2 are mutated in CLL and in other B-cell malignancies (13)(14)(15). A few EGR2-and NFKBIE-mutated patients have been reported in CLL (4,5,16). To further establish the importance of the early mutations identified in our patients, we investigated the recurrence of some of them by direct Sanger sequencing of the mutational hotspots of BRAF, EGR2, MED12, MYD88, NFKBIE, NOTCH1, SF3B1, TP53, and XPO1 in the 168 untreated patients with stage B and C CLL who were sampled at inclusion in a clinical trial (www.clinicaltrials.…”
Section: Early Mutations Affect Genes Recurrently Mutated In Cll and mentioning
confidence: 99%
“…Genes such as BRAF and MLL2 are mutated in CLL and in other B-cell malignancies (13)(14)(15). A few EGR2-and NFKBIE-mutated patients have been reported in CLL (4,5,16). To further establish the importance of the early mutations identified in our patients, we investigated the recurrence of some of them by direct Sanger sequencing of the mutational hotspots of BRAF, EGR2, MED12, MYD88, NFKBIE, NOTCH1, SF3B1, TP53, and XPO1 in the 168 untreated patients with stage B and C CLL who were sampled at inclusion in a clinical trial (www.clinicaltrials.…”
Section: Early Mutations Affect Genes Recurrently Mutated In Cll and mentioning
confidence: 99%
“…Frequent inactivating mutations, including a recurrent 4-bp deletion, of the NFKBIE gene, are seen in advanced stage CLL [73,99,100]. NFKBIE encodes a negative regulator of NFjB signaling in B cells, which is important for controlling the B-cell response to external stimuli, including TLR and BCR signaling [101].…”
Section: Implication Of the Bcr Tlr Pathwaysmentioning
confidence: 99%
“…Additional evidence in favor of targeting BCR signaling is found in the mutational studies showing clustering of somatic mutations in genes belonging to pathways involved in BTK downstream effectors, such as those found in PLC/Ca2 + signaling, including PLC, CAMK and NFAT (6 of 105 of the patients analyzed by Quesada et al). 17 This is also supported by the BCR downstream pathway mutations detected in the series by Domenech et al, 44 which affects KRAS, SMARCA2, NFK-BIE and PRKD3, all of which have been shown to play a role in BCR, NF-kB and related signaling pathways. 44 Additionally, members of the MAPK signaling pathway have been found mutated (e.g.…”
Section: Chronic Lymphocytic Leukemiamentioning
confidence: 73%
“…17 This is also supported by the BCR downstream pathway mutations detected in the series by Domenech et al, 44 which affects KRAS, SMARCA2, NFK-BIE and PRKD3, all of which have been shown to play a role in BCR, NF-kB and related signaling pathways. 44 Additionally, members of the MAPK signaling pathway have been found mutated (e.g. EGFR, FGFR2, KRAS, BRAF) 16,17 or with increased mRNA expression (e.g.…”
Section: Chronic Lymphocytic Leukemiamentioning
confidence: 73%
See 1 more Smart Citation